2022
DOI: 10.1016/j.erss.2021.102472
|View full text |Cite
|
Sign up to set email alerts
|

The office of the future: Operational energy consumption in the post-pandemic era

Abstract: As a result of COVID-19 and in order to combat the spread of the virus, work-from-home and remote working has become a widely accepted practice in professional settings globally. It is widely known that we are currently experiencing a highly transient period in terms of how we define work. Office work is progressively becoming more collaborative, modern workforce more mobile, and office occupancy more dynamic. As flexible working evolves, it becomes apparent that the role of workspace is also changing. So will… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…New hybrid work models bring new opportunities in this area. For example, Mantesi et al (2022) predicted that the energy demand in office buildings in the post-pandemic era could fall below the pre-pandemic level by as much as 50%.…”
Section: Key Insights From the Literaturementioning
confidence: 99%
“…New hybrid work models bring new opportunities in this area. For example, Mantesi et al (2022) predicted that the energy demand in office buildings in the post-pandemic era could fall below the pre-pandemic level by as much as 50%.…”
Section: Key Insights From the Literaturementioning
confidence: 99%
“…These measures restricted people's activities in different types buildings, and thus affected the energy consumption pattern accordingly. Recent studies have consistently identified energy consumption increases in the residential sector [ [5] , [6] , [7] , [8] ] while decreases in the non-residential sector such as university buildings [ [9] , [10] , [11] ], municipal buildings [ 12 ], commercial buildings [ 13 ] and offices [ 14 ]. Although these studies confirmed the significant impact, it is unclear whether the impact is continuing, which is an important question to explore further for managing the energy profiles in the post-pandemic era.…”
Section: Introductionmentioning
confidence: 99%
“…Since the COVID-19 pandemic began, commercial and institutional buildings now experience weeks and even months of below-normal occupancy due to increased use of remote work and learning. It has been acknowledged that offices must become flexible spaces because employees have indicated that working remotely 2-3 days a week lowers the amount of work-life conflict and are predicted that remote working will become the norm (Mantesi et al, 2022). As buildings fluctuate between periods of below-normal and normal occupancy, water quality studies are needed to understand how building water systems are behaving.…”
Section: Introductionmentioning
confidence: 99%